Pengembangan Bahan Ajar Fluida Statis Terintegrasi Google Classroom Untuk Meningkatkan Belajar Mandiri Peserta Didik - Anderias Henukh; Martha Loupatty; Supriyadi Supriyadi (Musamus Journal of Science Education, 2022)
The purpose of this study is to describe the results of developing integrated static fluid teaching materials in Google Classroom and improving students' independent learning outcomes. The research method used is research and development using the ADDIE model. The research subjects are information systems students with a total of 65 people. The instrument used is a validation sheet. In addition, it also uses a questionnaire to assess students' independent learning outcomes. The validity of the research instrument uses the product moment and the reliability uses the KR-20. The results of the validation of material experts, media experts, and linguists got an average score of 92.33. Analysis of students' self-study obtained an average score of 88. Based on these data, it can be concluded that the development of integrated static fluid teaching materials in Google Classroom can improve students' independent learning.